Profile of Primary Pediatric Brain and Spinal Cord Tumors from North India - Shirazi, Nadia (Indian J Med Paediatr Oncol, 2017)
BACKGROUND AND OBJECTIVE: The study was carried out to find the profile of pediatric brain and spinal cord tumors during 2006–2015 in a tertiary referral center of North India. MATERIALS AND METHODS: It was a retrospective medical record-based observational study. All children <18 years of age with confirmed histopathological diagnosis of cancer were included in the study. RESULTS: Central nervous system (CNS) tumors constituted 5.6% of all pediatric solid malignancies in our hospital. A total of 54 brain tumors and 13 spinal cord tumors were studied. Medulloblastoma was the most common brain tumor (20.3%) followed by pilocytic astrocytoma (16.6%) and glioblastoma multiforme (9.2%). The most common spinal cord tumor was Ewing's sarcoma/primitive neuroectodermal tumor (30.7%) followed by ependymoma (23%). Mean age was 10.5 years and 12.1 years for brain and spinal cord tumors, respectively. There was male predominance in brain tumors while the sex ratio was almost equal in spinal cord tumors. Histomorphologically, necrosis and angiogenesis were associated with higher grades of tumor. Approximately 35% children were alive after a mean follow-up of 36 ± 6 months. CONCLUSION: Compared with most international studies, we found a higher percentage of medulloblastoma in the brain, thus stressing the role of regional and ethnic influences in the pathogenesis of CNS tumors.